Air electrode material for solid oxide cells and preparation and use thereof

CN122930933APending Publication Date: 2026-10-16ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611421922.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的目的在于解决现有可逆固体氧化物电池的空气电极在宽温度区间内难以兼顾高功率密度和电化学稳定性的问题,提供一种固体氧化物电池的空气电极材料及其制备和应用

Benefits of technology

[0027] The chemical formula of the air electrode material for the solid oxide battery provided by this invention is Nd. 0.5Ba 0.5- x Sr x Co 0.8 Fe 0.2 O 3-δ Where x represents the Sr doping amount, 0.1≤x≤0.5, and δ is the oxygen vacancy content. This is achieved through Nd... 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ By doping the A-site with different amounts of Sr, the Sr can partially replace the Ba, thereby stabilizing the phase structure of the air electrode material and improving its electrical conductivity and catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930933A_ABST
    Figure CN122930933A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solid oxide batteries, and discloses an air electrode material of a solid oxide battery and preparation and application of the air electrode material. 0.5 Ba 0.5‑x Sr x Co 0.8 Fe 0.2 O 3‑δ , wherein 0.1<=x<=0.5, and delta is the oxygen vacancy content. The preparation method comprises the following steps: dissolving corresponding metal nitrate in deionized water, adding ethylenediaminetetraacetic acid, citric acid and ammonia water, adjusting the pH value, and heating to form a gel, and then drying and calcining to obtain the air electrode material. The air electrode material can be used in proton ceramic fuel cells and oxygen ion conductor type reversible solid oxide batteries, and has low polarization impedance, high output performance and good running stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid oxide battery technology, and more particularly to an air electrode material for solid oxide batteries, its preparation, and its application. Background Technology

[0002] Wind and solar energy are characterized by significant intermittency and volatility. Large-scale grid integration can easily lead to power imbalances, wind curtailment, and solar power curtailment. Therefore, developing long-duration, high-efficiency energy storage technologies is crucial for building new power systems. Existing mainstream energy storage technologies each have certain limitations. For example, pumped hydro storage is severely restricted by geographical conditions; lithium batteries are more suitable for short-term energy storage and struggle to achieve large-scale, cross-seasonal energy storage; and cryogenic electrolyzer and fuel cell coupling systems suffer from low equipment utilization and high investment costs.

[0003] Reversible solid oxide batteries can utilize renewable energy sources and waste heat generated in industrial processes as energy inputs, thereby reducing electricity consumption and improving energy efficiency. Reversible solid oxide batteries can achieve fuel cell power generation and hydrogen electrolysis in the same device, serving as intermittent power generation devices and energy conversion equipment. They offer advantages such as fast start-up, high conversion efficiency, and low system cost, making them an important electrochemical technology for renewable energy consumption and hydrogen storage.

[0004] However, the long-term stability of reversible solid oxide batteries is limited by the performance of the air electrode. The oxygen reduction and oxygen evolution reactions on the air electrode are relatively slow, which significantly increases the polarization loss of the battery. In fuel cell mode, the concentration polarization and activation polarization of the air electrode increase, resulting in a decrease in the operating voltage under the same current conditions, and thus a decrease in the output power density. In electrolyzer mode, the external voltage required for electrolysis increases, energy consumption increases, which in turn leads to a decrease in hydrogen production efficiency and accelerates material degradation.

[0005] Developing a dual-functional air electrode suitable for both medium and high-temperature operating conditions is beneficial for broadening the operating temperature range of reversible solid oxide batteries, allowing the battery to flexibly select different operating temperatures according to operating conditions. An air electrode with good wide-temperature thermochemical stability can suppress interfacial delamination and failure between the air electrode and electrolyte caused by thermal cycling, and is compatible with different electrolyte systems, thereby improving the versatility of air electrode materials. Simultaneously, the air electrode maintains high oxygen reduction and oxygen evolution reactivity over a wide temperature range, which is beneficial for improving the round-trip energy efficiency of reversible solid oxide batteries and reducing the system's requirements for high-temperature components.

[0006] Therefore, it is necessary to develop a solid oxide battery air electrode material with high reactivity and stability that can withstand both medium and high temperature operating conditions, in order to improve battery durability and system operation flexibility.

[0007] Among existing air electrode materials, Ba is the most common. 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ Cobalt-based perovskite materials, represented by Sr, are widely used due to their high oxygen reduction reactivity, high oxygen vacancy concentration, and mixed ion-electron conductivity. However, during long-term operation, Sr elements at the A-sites tend to spontaneously segregate to the material surface and form an insulating SrO phase, leading to a degradation in the performance of the air electrode. Therefore, how to suppress Sr surface segregation while maintaining the reactivity of the air electrode and improve its stability during long-term operation remains a technical problem that needs to be solved in this field. Summary of the Invention

[0008] The purpose of this invention is to solve the problem that the air electrode of existing reversible solid oxide batteries is difficult to balance high power density and electrochemical stability over a wide temperature range, and to provide an air electrode material for solid oxide batteries, as well as its preparation and application.

[0009] The air electrode material provided by this invention is perovskite material Nd 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ Where 0.1≤x≤0.5, and δ is the oxygen vacancy content. This is achieved through Nd... 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ Different amounts of Sr are doped at the A-site to partially replace Ba, thereby improving the performance and stability of the air electrode material.

[0010] The air electrode material provided by this invention has a small polarization resistance and can achieve high output performance when applied to proton ceramic fuel cells and oxygen ion conductor type solid oxide batteries. In particular, when applied to oxygen ion conductor type reversible solid oxide batteries, it can achieve high power output under medium and high temperature operating conditions and exhibits good long-term operating stability and anti-degradation ability under high temperature conditions.

[0011] To achieve the above objectives, the present invention adopts the following technical solution:

[0012] An air electrode material for a solid oxide battery, the air electrode material having the chemical formula Nd 0.5 Ba 0.5- x Srx Co 0.8 Fe 0.2 O 3-δ Where 0.1≤x≤0.5, and δ is the oxygen vacancy content.

[0013] Preferably, x=0.2, and the chemical formula of the air electrode material is Nd. 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ It is a cubic crystal system.

[0014] A method for preparing the above-mentioned air electrode material includes the following steps:

[0015] Step 1: According to the stoichiometric ratio of Nd, Ba, Sr, Co and Fe in the air electrode material, dissolve Nd(NO3)3·6H2O, Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O and Fe(NO3)3·9H2O in deionized water to obtain a metal salt solution. When x=0.5, Ba(NO3)2 is not added.

[0016] Step 2: Add ethylenediaminetetraacetic acid, citric acid and ammonia to the metal salt solution, adjust the pH value, and heat and stir until a gel is formed;

[0017] Step 3: The gel is dried and calcined sequentially to obtain the air electrode material of the solid oxide battery.

[0018] Preferably, in step 2, the pH value is adjusted to 6-8.

[0019] Preferably, the drying temperature is 180~250℃ and the time is 1~10 h; the calcination temperature is 900~1100℃ and the time is 1~10 h, with a heating rate of 1~10℃ / min.

[0020] Preferably, the molar ratio of total metal ions, ethylenediaminetetraacetic acid, and citric acid in the metal salt solution is 1:a:b, where 0 < a ≤ 1.2 and 1 ≤ b ≤ 3.

[0021] The application of the above-mentioned air electrode materials in the air electrode of solid oxide batteries.

[0022] Preferably, the solid oxide battery is a proton ceramic fuel cell, and the electrolyte of the proton ceramic fuel cell is BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The fuel electrode is Ni-BaZr.0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Composite fuel electrode.

[0023] Preferably, the solid oxide battery is an oxygen ion conductor type reversible solid oxide battery, and the electrolyte of the oxygen ion conductor type reversible solid oxide battery is (Y2O3). 0.08 (ZrO2) 0.92 The fuel electrode is Ni-(Y2O3). 0.08 (ZrO2) 0.92 Composite fuel electrode.

[0024] Preferably, a GDC barrier layer is provided between the air electrode and the electrolyte.

[0025] In this specification, GDC refers to gadolinium-doped cerium oxide, with the chemical formula Ce. 0.9 Gd 0.1 O 2-δ BZCYYb refers to the chemical formula BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ YSZ refers to a proton conductor material; it is composed of (Y₂O₃). 0.08 (ZrO2) 0.92 Oxygen ion conductor materials; NBCF refers to undoped Sr material with the chemical formula Nd. 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ Perovskite materials; unless otherwise specified, NBSCF refers to perovskite materials with an Sr doping level of x of 0.2 and a chemical formula of Nd. 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ Air electrode materials. For Nd... 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ Furthermore, materials with different Sr doping levels are distinguished by their corresponding complete chemical formulas or x values.

[0026] The beneficial effects of this invention are as follows:

[0027] The chemical formula of the air electrode material for the solid oxide battery provided by this invention is Nd. 0.5Ba 0.5- x Sr x Co 0.8 Fe 0.2 O 3-δ Where x represents the Sr doping amount, 0.1≤x≤0.5, and δ is the oxygen vacancy content. This is achieved through Nd... 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ By doping the A-site with different amounts of Sr, the Sr can partially replace the Ba, thereby stabilizing the phase structure of the air electrode material and improving its electrical conductivity and catalytic activity.

[0028] Testing of symmetrical cells fabricated using the aforementioned air electrode material as an electrode revealed that Sr doping reduces the polarization impedance of the air electrode material and enhances its oxygen reduction and oxygen evolution reactivity. When applied to proton ceramic fuel cells and oxygen-ion conductor type solid oxide batteries, the air electrode material achieves high output power density. Therefore, Sr doping improves the reactivity of the air electrode material under both fuel cell and electrolyzer modes, and ensures the stability of oxygen-ion conductor type reversible solid oxide batteries using the air electrode material during switching between fuel cell and electrolyzer modes.

[0029] When x = 0.2, the chemical formula of the air electrode material is Nd. 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ Abbreviated as NBSCF. An oxygen-ion conductor type reversible solid oxide battery, NBSCF|GDC|YSZ|Ni-YSZ, fabricated using NBSCF as the air electrode, GDC as the barrier layer, YSZ as the electrolyte, and Ni-YSZ as the composite fuel electrode, achieved a maximum output power density of 1370 mW·cm³ at 800℃, 750℃, and 700℃ when operating in fuel cell mode under H₂ atmosphere. -2 970mW·cm -2 and 610 mW·cm -2 In electrolytic cell mode, the current density reaches 1.35 A·cm at an electrolysis voltage of 1.3 V, 800℃, 750℃, and 700℃. -2 0.6 A·cm -2 and 0.3 A·cm -2 .

[0030] The proton ceramic fuel cell NBSCF|BZCYYb|Ni-BZCYYb, fabricated using NBSCF as the air electrode, BZCYYb as the electrolyte, and Ni-BZCYYb as the composite fuel electrode, achieved a maximum output power density of 1270 mW·cm⁻¹ at 700℃, 650℃, 600℃, and 550℃ under H₂ atmosphere. -2 860 mW·cm -2 540 mW·cm -2 and 210 mW·cm -2 The above results demonstrate that the air electrode material is suitable for both proton ceramic fuel cells and oxygen ion conductor type reversible solid oxide batteries, and exhibits good electrochemical performance at different operating temperatures. Attached Figure Description

[0031] Figure 1 Nd2 without Sr doping 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ Materials and Nd with different Sr element doping levels 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ The X-ray diffraction pattern of the air electrode material after calcination at 1000℃ for 5 h was obtained by testing at 25℃, where 0.1≤x≤0.5.

[0032] Figure 2 Electrochemical impedance spectroscopy (EIS) spectra of symmetrical cells NBCF|BZCYYb|NBCF and NBSCF|BZCYYb|NBSCF, prepared using NBCF and NBSCF as air electrodes and BZCYYb as electrolyte, were obtained at 500–700 °C in air and air atmospheres containing 3% water vapor, respectively. (a), (b), (c), and (d) represent the test results under different air electrode materials and test atmospheres.

[0033] Figure 3 The activation energy fitting diagrams for NBCF and NBSCF air electrodes in an air atmosphere containing 3% water vapor are calculated based on the polarization impedance at different temperatures.

[0034] Figure 4 In the figure, (a) is a comparison of the electrochemical impedance spectra of NBCF and NBSCF air electrodes obtained at 600℃ in an air atmosphere containing 3% water vapor, and (b) is the deconvolution peak diagram obtained after analyzing the relaxation time distribution of the electrochemical impedance spectra of the two air electrode materials.

[0035] Figure 5 Electrochemical impedance spectra of symmetrical cells NBCF|GDC|NBCF and NBSCF|GDC|NBSCF prepared with NBCF and NBSCF as air electrodes and GDC as electrolyte, respectively, were obtained in air atmosphere and at 650~800℃. Among them, (a) is the test result of NBCF symmetrical cell and (b) is the test result of NBSCF symmetrical cell.

[0036] Figure 6 The current-voltage-power density curves of a proton ceramic fuel cell prepared with BZCYYb as electrolyte and Ni-BZCYYb as composite fuel electrode are obtained by testing at 550~700℃. Among them, (a) is the test result of single cell NBSCF|BZCYYb|Ni-BZCYYb, and (b) is the test result of single cell NBCF|BZCYYb|Ni-BZCYYb.

[0037] Figure 7 Electrochemical impedance spectroscopy (EIS) spectra of a symmetrical cell NBSCF|GDC|NBSCF prepared using NBSCF as the air electrode and GDC as the electrolyte were obtained under air atmosphere and air atmosphere containing 1% carbon dioxide. These spectra were used to characterize the carbon dioxide tolerance of the NBSCF air electrode material.

[0038] Figure 8 The current-voltage-power density curves of an oxygen-ion conductor solid oxide battery, prepared with GDC as a barrier layer, YSZ as an electrolyte, and Ni-YSZ as a composite fuel electrode, were obtained under fuel cell mode at 700-800℃. Among them, (a) is the test result of a single cell NBSCF|GDC|YSZ|Ni-YSZ, and (b) is the test result of a single cell NBCF|GDC|YSZ|Ni-YSZ.

[0039] Figure 9 The current-voltage curves of a single-cell NBSCF|GDC|YSZ|Ni-YSZ were obtained by testing at 700~800℃ in steam electrolysis mode.

[0040] Figure 10 The stability curves are obtained from alternating cycle tests of a single cell NBSCF|GDC|YSZ|Ni-YSZ at 700℃ in fuel cell mode and electrolyzer mode.

[0041] Figure 11 For single-cell NBSCF|GDC|YSZ|Ni-YSZ at 700℃ and 500 mA·cm -2 The stability curve obtained from long-term electrolysis tests at a current density.

[0042] Figure 12 This is a cross-sectional scanning electron microscope image of a single-cell NBSCF|GDC|YSZ|Ni-YSZ after long-term stability testing. Detailed Implementation

[0043] To provide a clearer understanding of the technical features, objectives, and beneficial effects of this invention, the technical solution of this invention is described in detail below, but this should not be construed as limiting the scope of implementation of this invention. Unless otherwise specified, the methods used in this invention are conventional methods in this technical field. In this invention, materials, reagents, or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0044] In one embodiment, the present invention provides an air electrode material for a solid oxide battery, the air electrode material having the chemical formula Nd. 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ Where x represents the Sr doping amount, 0.1≤x≤0.5, and δ is the oxygen vacancy content. The air electrode material can be applied to reversible solid oxide batteries (R-SOC).

[0045] The air electrode material is made from perovskite material Nd 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ Different amounts of Sr are doped at the A site to partially replace Ba, thereby stabilizing the phase structure of the material and reducing polarization resistance. This also enables the air electrode material to exhibit excellent electrochemical performance in both oxygen ion conductor solid oxide batteries and proton ceramic fuel cells.

[0046] Tests showed that, at 800°C, the maximum output power density of the oxygen ion conductor type solid oxide battery NBSCF|GDC|YSZ|Ni-YSZ using the aforementioned air electrode material was 1370 mW·cm⁻¹. -2 At 700°C, the maximum output power density of the proton ceramic fuel cell NBSCF|BZCYYb|Ni-BZCYYb using the aforementioned air electrode material is 1270 mW·cm⁻¹. -2 In comparison, the maximum output power densities of undoped Sr single cells NBCF|GDC|YSZ|Ni-YSZ and NBCF|BZCYYb|Ni-BZCYYb at 800℃ and 700℃ are 1020 mW·cm⁻¹, respectively. -2 and 850 mW·cm-2 Compared to the corresponding undoped Sr single cells, the maximum output power density of oxygen-ion conductor solid oxide batteries and proton ceramic fuel cells using the aforementioned air electrode material is increased by 34.3% and 49.4%, respectively.

[0047] In a preferred embodiment of the present invention, x=0.2, and the chemical formula of the air electrode material is Nd. 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ It is a cubic crystal system.

[0048] In one embodiment, the present invention provides a method for preparing the above-mentioned air electrode material, characterized by comprising the following steps:

[0049] Step 1: According to the stoichiometric ratio of Nd, Ba, Sr, Co and Fe in the air electrode material, dissolve Nd(NO3)3·6H2O, Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O and Fe(NO3)3·9H2O in deionized water to obtain a metal salt solution. When x=0.5, Ba(NO3)2 is not added.

[0050] Step 2: Add ethylenediaminetetraacetic acid, citric acid and ammonia to the metal salt solution, adjust the pH to 6-8, and heat and stir until a gel is formed;

[0051] Step 3: The gel is dried and calcined sequentially to obtain the powder of the air electrode material of the solid oxide battery.

[0052] In a preferred embodiment of the present invention, the drying temperature is 180~250℃ and the time is 1~10 h; the calcination temperature is 900~1100℃ and the time is 1~10 h, and the heating rate is 1~10℃ / min.

[0053] In a preferred embodiment of the present invention, the molar ratio of total metal ions, ethylenediaminetetraacetic acid and citric acid in the metal salt solution is 1:a:b, wherein 0 < a ≤ 1.2 and 1 ≤ b ≤ 3.

[0054] In one embodiment, the present invention proposes the application of the above-mentioned air electrode material in the air electrode of a solid oxide battery, which can increase the stability of the battery, improve the catalytic activity of the battery air electrode, and reduce the polarization resistance and activation energy of the electrochemical reaction.

[0055] In a preferred embodiment of the present invention, the solid oxide battery is a proton ceramic fuel cell, and the electrolyte of the proton ceramic fuel cell is BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The fuel electrode is Ni-BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ A composite fuel electrode, wherein the raw materials for preparing the composite fuel electrode include NiO and BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The three components, polyvinyl butyral, are in a mass ratio of 6:(1~4):(0.25~1), wherein the polyvinyl butyral is used as a pore-forming agent.

[0056] In a preferred embodiment of the present invention, the solid oxide battery is an oxygen ion conductor type reversible solid oxide battery, and the electrolyte of the oxygen ion conductor type reversible solid oxide battery is (Y2O3). 0.08 (ZrO2) 0.92 The fuel electrode is Ni-(Y2O3). 0.08 (ZrO2) 0.92 A composite fuel electrode, wherein a GDC barrier layer is provided between the air electrode and the electrolyte, and the raw materials for preparing the composite fuel electrode include NiO and (Y2O3). 0.08 (ZrO2) 0.92 The three components, polyvinyl butyral, are in a mass ratio of 6:(1~4):(0.25~1), wherein the polyvinyl butyral is used as a pore-forming agent.

[0057] In a preferred embodiment of the present invention, the application includes alternating operation of the oxygen ion conductor type reversible solid oxide battery in fuel cell mode and electrolyzer mode at 700°C, wherein 0.5 A·cm⁻¹ is applied in fuel cell mode. -2 The current density is -0.5 A·cm⁻¹ applied in electrolytic cell mode. -2 The current density.

[0058] The specific implementation of the present invention will be described in detail below with reference to specific embodiments.

[0059] Example 1: This example provides Nd... 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2O 3-δ The preparation method of air electrode material for solid oxide batteries, wherein x is 0.1, is as follows.

[0060] S1: Preparation of Nd 0.5 Ba 0.4 Sr 0.1 Co 0.8 Fe 0.2 O 3-δ When preparing the air electrode material, with x=0.1, 2.1918 g of Nd(NO3)3·6H2O, 1.0453 g of Ba(NO3)2, 0.2116 g of Sr(NO3)2, 2.3282 g of Co(NO3)2·6H2O, and 0.8080 g of Fe(NO3)3·9H2O were weighed and dissolved in a small amount of deionized water to obtain a metal salt solution. Following a molar ratio of ethylenediaminetetraacetic acid (EDTA), citric acid, and total metal ions of 1:2:1, 5.8448 g of EDTA and 7.6848 g of citric acid were weighed as complexing agents and dissolved in deionized water to obtain a complexing agent solution.

[0061] S2: Add the complexing agent solution to the corresponding metal salt solution, add an appropriate amount of ammonia water, and adjust the pH of the resulting solution to about 7. Place the rotor into the solution and continuously heat and stir on a magnetic stirrer until the water is completely evaporated, obtaining a gel-like substance.

[0062] S3: Remove the rotor from the gel-like substance and seal the mouth of the beaker with perforated aluminum foil to prevent the gel-like substance from overflowing during the drying process. Then place the beaker containing the gel-like substance into a forced-air drying oven and dry it at a constant temperature of 180°C for 10 hours to obtain a fluffy and porous precursor.

[0063] S4: Remove the beaker from the drying oven and allow it to cool. Then, use a scraper to scrape the precursor into the crucible. Place the crucible containing the precursor in a high-temperature muffle furnace and calcine it at 1000°C for 5 hours. After calcination and cooling, the corresponding air electrode material powder for solid oxide batteries is obtained.

[0064] Example 2: This example provides Nd... 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ The preparation method of air electrode material for solid oxide batteries, wherein x is 0.2, is as follows.

[0065] S1: Preparation of Nd 0.5Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ When preparing the air electrode material, with x=0.2, 2.1918 g of Nd(NO3)3·6H2O, 0.7840 g of Ba(NO3)2, 0.4233 g of Sr(NO3)2, 2.3282 g of Co(NO3)2·6H2O, and 0.8080 g of Fe(NO3)3·9H2O were weighed and dissolved in a small amount of deionized water to obtain a metal salt solution. Following a molar ratio of ethylenediaminetetraacetic acid (EDTA), citric acid, and total metal ions of 1:2:1, 5.8448 g of EDTA and 7.6848 g of citric acid were weighed as complexing agents and dissolved in deionized water to obtain a complexing agent solution.

[0066] S2: Add the complexing agent solution prepared in S1 of this embodiment to the metal salt solution prepared in S1 of this embodiment, and the subsequent operations are the same as S2 of Example 1.

[0067] S3 and S4 are the same as in Example 1.

[0068] Example 3: This example provides Nd... 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ The preparation method of air electrode material for solid oxide batteries, wherein x is 0.5, is as follows.

[0069] S1: Preparation of Nd 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ When preparing the air electrode material, with x=0.5, 2.1918 g of Nd(NO3)3·6H2O, 1.0582 g of Sr(NO3)2, 2.3282 g of Co(NO3)2·6H2O, and 0.8080 g of Fe(NO3)3·9H2O were weighed and dissolved in a small amount of deionized water to obtain a metal salt solution. Since the stoichiometric coefficient of Ba is 0 when x=0.5, Ba(NO3)2 was not added. Following a molar ratio of ethylenediaminetetraacetic acid (EDTA), citric acid, and total metal ions of 1:2:1, 5.8448 g of EDTA and 7.6848 g of citric acid were weighed as complexing agents and dissolved in deionized water to obtain a complexing agent solution.

[0070] S2: Add the complexing agent solution prepared in S1 of this embodiment to the metal salt solution prepared in S1 of this embodiment, and the subsequent operations are the same as S2 of Example 1.

[0071] S3 and S4 are the same as in Example 1.

[0072] Example 4: This example provides a Ni-BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ A method for preparing composite fuel electrode powder, wherein BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The composite fuel electrode powder is abbreviated as BZCYYb, and the specific steps are as follows.

[0073] S1: Weigh 3 g of NiO, 2 g of BZCYYb powder, and 0.25 g of polyvinyl butyral. Pour all the NiO, BZCYYb powder, and polyvinyl butyral into a ball mill jar, add an appropriate amount of anhydrous ethanol, and ball mill for 120 min. The polyvinyl butyral is used as a pore-forming agent.

[0074] S2: Transfer the composite fuel electrode powder slurry obtained after ball milling to a mortar, place a rotor in the mortar, and place the mortar on a magnetic stirrer to accelerate the evaporation of anhydrous ethanol under sodium lamp irradiation until the anhydrous ethanol is completely evaporated.

[0075] S3: The composite fuel electrode powder is scraped out of the mortar using a scraper, and then placed in a constant temperature drying oven at 80°C for 10 h to obtain Ni-BZCYYb composite fuel electrode powder.

[0076] Example 5: This example provides a method for preparing a proton ceramic fuel cell, which includes an air electrode, an electrolyte, and a fuel electrode. The air electrode material is Nd2 prepared in Example 2. 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ The structure of the proton ceramic fuel cell is abbreviated as NBSCF; the electrolyte is BZCYYb; the fuel electrode is the Ni-BZCYYb composite fuel electrode prepared in Example 4. The specific steps are as follows.

[0077] S1: Weigh 0.40 g of the Ni-BZCYYb composite fuel electrode powder prepared in Example 4, place it in a mold, and press it into a sheet with a diameter of about 15 mm using a tablet press to obtain a fuel electrode green blank.

[0078] S2: Weigh 1 g of BZCYYb powder and place it in a glass bottle. Add 15 mL of anhydrous ethanol, shake and mix thoroughly, then place the resulting mixture in an ultrasonic cleaning tank and sonicate for 30 min. Take 1.5 mL of the mixture and load it into a spray gun. Under high-temperature sodium lamp irradiation, spray the mixture evenly onto the fuel electrode green body. After the anhydrous ethanol has completely evaporated, use a tablet press to press the electrolyte and fuel electrode green body together to form a fuel electrode-electrolyte bilayer green body. Sinter the fuel electrode-electrolyte bilayer green body at 1450℃ for 5 h to obtain a fuel electrode-supported half-cell bilayer sheet.

[0079] S3: Place the half-cell bilayer sheet on a heating platform and set the temperature of the heating platform to 130℃. After the half-cell bilayer sheet is uniformly and fully heated, use a spray gun to uniformly spray the NBSCF air electrode slurry onto the electrolyte side, forming a three-layer structure of air electrode-electrolyte-fuel electrode. Place the three-layer structure of air electrode-electrolyte-fuel electrode in a muffle furnace for calcination at a temperature of 900~1100℃, a heating rate of 5℃ / min, and a holding time of 2 h. After calcination and cooling, remove the material to obtain the proton ceramic fuel cell NBSCF|BZCYYb|Ni-BZCYYb.

[0080] Example 6: This example provides a method for preparing an oxygen-ion conductor type reversible solid oxide battery. The oxygen-ion conductor type reversible solid oxide battery includes an air electrode, a barrier layer, an electrolyte, and a fuel electrode. The air electrode material is Nd2 prepared in Example 2. 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ It is abbreviated as NBSCF; the barrier layer is a GDC barrier layer; the electrolyte is (Y2O3). 0.08 (ZrO2) 0.92 The structure of the oxygen ion conductor type reversible solid oxide battery is abbreviated as YSZ; the fuel electrode is a Ni-YSZ composite fuel electrode, and the specific steps are as follows.

[0081] S1: Weigh 0.40 g of Ni-YSZ composite fuel electrode powder. The preparation method of the Ni-YSZ composite fuel electrode powder is the same as that of the Ni-BZCYYb composite fuel electrode powder in Example 4, except that YSZ powder is used instead of BZCYYb powder. Place the Ni-YSZ composite fuel electrode powder into a mold and press it into a sheet with a diameter of about 15 mm using a tablet press to obtain a fuel electrode green blank.

[0082] S2: Weigh 1 g of YSZ powder and place it in a glass bottle. Add 15 mL of anhydrous ethanol, shake and mix thoroughly, then place the resulting mixture in an ultrasonic cleaning tank and sonicate for 30 min. Take 1.5 mL of the mixture and load it into a spray gun. Under high-temperature sodium lamp irradiation, spray the mixture evenly onto the fuel electrode green body. After the anhydrous ethanol has completely evaporated, use a tablet press to press the electrolyte and fuel electrode green body together to form a fuel electrode-electrolyte bilayer green body. Sinter the fuel electrode-electrolyte bilayer green body at 1450℃ for 5 h to obtain a fuel electrode-supported half-cell bilayer sheet.

[0083] S3: Place the half-cell bilayer sheet on a heating platform and set the platform temperature to 130℃. After the half-cell bilayer sheet is uniformly and fully heated, use a spray gun to uniformly spray the GDC barrier layer slurry onto the electrolyte side, forming a three-layer structure of barrier layer-electrolyte-fuel electrode. Place the barrier layer-electrolyte-fuel electrode three-layer structure in a muffle furnace for calcination at a temperature of 900~1300℃, a heating rate of 5℃ / min, and a holding time of 2 h. After calcination and cooling, remove the sheet to obtain the half-cell bilayer sheet.

[0084] S4: Place the three-layer half-cell sheet on a heating platform and set the temperature of the heating platform to 130℃. After the three-layer half-cell sheet is uniformly and fully heated, use a spray gun to uniformly spray NBSCF air electrode slurry onto one side of the barrier layer, forming a four-layer structure of air electrode-barrier layer-electrolyte-fuel electrode. Place the four-layer structure of air electrode-barrier layer-electrolyte-fuel electrode in a muffle furnace for calcination at a temperature of 900~1100℃, a heating rate of 5℃ / min, and a holding time of 2 h. After calcination and cooling, remove the battery to obtain an oxygen ion conductor type reversible solid oxide battery NBSCF|GDC|YSZ|Ni-YSZ.

[0085] To further illustrate the phase structure, electrochemical reactivity, and application performance of the air electrode material provided by this invention in solid oxide batteries, the air electrode material prepared in the examples, as well as symmetrical batteries and single cells prepared from this air electrode material, were tested. In the following tests, NBSCF represents Nd... 0.5 Ba0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ The air electrode material, NBCF indicates undoped Sr Nd. 0.5 Ba 0.5 Co 0.8 Fe 0.2 O 3-δ Materials. Unless otherwise specified, the proton ceramic fuel cell uses BZCYYb as the electrolyte and Ni-BZCYYb as the composite fuel electrode, while the oxygen ion conductor type reversible solid oxide battery uses YSZ as the electrolyte, GDC as the barrier layer, and Ni-YSZ as the composite fuel electrode.

[0086] Test Example 1: This test example analyzes the phase structure of NBCF and NBSCF obtained after doping with different amounts of Sr. The corresponding powders were calcined at 1000℃ for 5 h and X-ray diffraction was performed at room temperature. The obtained XRD patterns are shown below. Figure 1 As shown in the diagram, the peak height and width of the diffraction peaks indicate that the powder has formed a phase after calcination.

[0087] Undoped NBCF exhibits a distinct thermodynamic metastable phase, and its structure is prone to collapse at high temperatures. When the Sr doping concentration x is 0.1, Nd2+ is present in the material. 0.5 Sr 0.5 The CoO3 impurity phase is prone to A-site element segregation under high temperature conditions, forming insulating phases such as SrO and SrCO3, which leads to a decrease in the electrical conductivity of the material.

[0088] When the Sr doping amount x is 0.2, the crystal structure of the material changes from the tetragonal crystal system of NBCF to the stable cubic crystal system of NBSCF, exhibiting the strongest thermodynamic spontaneous stabilization tendency. Compared with the tetragonal crystal system, the cubic NBSCF does not exhibit anisotropic thermal expansion differences and is less prone to microcracks due to lattice distortion under long-term high-temperature conditions.

[0089] When the Sr doping amount x is 0.3 and 0.4, the phase structure of the material changes back to a tetragonal crystal system; when the Sr doping amount x is 0.5, the phase structure of the material changes to an orthorhombic crystal system, which has the greatest degree of lattice distortion and is prone to microcracks under long-term high-temperature conditions.

[0090] As the Sr doping concentration gradually increases, the probability of Sr segregation to form SrO and SrCO3 insulating phases also gradually increases. Since the radius of Sr ions is smaller than that of Ba ions, Sr ions cause lattice contraction after entering the perovskite lattice, causing the main diffraction peak of NBSCF to gradually shift to higher angles, indicating that Sr elements have successfully entered the perovskite lattice.

[0091] Test Example 2: This test example tests the performance of proton conductor symmetric cells and oxygen ion conductor symmetric cells prepared using NBCF and NBSCF as air electrode materials.

[0092] In the proton conductor symmetric cell test, the prepared symmetric cell is placed in an experimental furnace, exposing the cell to an air atmosphere, or the atmosphere is switched to an air atmosphere containing 3% water vapor. The airflow rate and the test temperature of the symmetric cell are controlled, and the electrochemical impedance spectra of the symmetric cells NBSCF|BZCYYb|NBSCF and NBCF|BZCYYb|NBCF are tested at different temperatures.

[0093] Figure 2 Images (a), (b), (c), and (d) show the electrochemical impedance spectra of two symmetrical cells under different test temperatures and atmospheres. Figure 2 It can be seen that, regardless of whether it is in an air atmosphere or an air atmosphere containing 3% water vapor, the polarization resistance of the NBSCF symmetric cell is less than that of the NBCF symmetric cell. This indicates that the oxygen reduction reaction activity of the NBSCF air electrode material and its ability to absorb moisture and form proton-related defects are superior to those of NBCF.

[0094] Figure 3 The activation energies of NBCF and NBSCF in an air atmosphere containing 3% water vapor are shown. The activation energy of NBCF is 129.9 kJ·mol⁻¹. -1 The activation energy of NBSCF is 108.5 kJ·mol⁻¹. -1 The above results indicate that the reaction energy barrier of NBSCF in electrochemical reaction processes such as oxygen surface exchange, oxygen vacancy migration, and gas-phase mass transfer is lower than that of NBCF, suggesting that NBSCF has better performance in oxygen reduction reaction and oxygen evolution reaction kinetics.

[0095] Figure 4 Figure (a) shows a comparison of the electrochemical impedance spectroscopy (EIS) results of NBCF and NBSCF at 600 °C in an air atmosphere containing 3% water vapor. The polarization impedances of NBCF and NBSCF are 1.350 Ω·cm. 2 and 0.398 Ω·cm 2 Compared to NBCF, NBSCF exhibits a reduction in polarization impedance of approximately 70.5%.

[0096] Figure 4 (b) shows the deconvolution peaks obtained after relaxation time distribution analysis of the corresponding electrochemical impedance spectroscopy. Based on frequency range, the deconvolution peaks are divided into high-frequency, mid-frequency, and low-frequency regions. The high-frequency region reflects charge transfer processes, the mid-frequency region reflects ion transport or surface exchange processes, and the low-frequency region reflects surface oxygen diffusion processes. The ion transport or surface exchange processes corresponding to the mid-frequency region are the main limiting steps affecting electrochemical reactions. The peak areas of NBSCF in the high-frequency, mid-frequency, and low-frequency regions are all smaller than those of NBCF, indicating that NBSCF has a faster ion diffusion rate and surface exchange rate.

[0097] In the oxygen ion conductor symmetric cell test, the prepared symmetric cell was placed in an experimental furnace, exposing the cell to an air atmosphere. The air intake flow rate and the test temperature of the symmetric cell were controlled, and the electrochemical impedance spectra of the symmetric cells NBSCF|GDC|NBSCF and NBCF|GDC|NBCF were tested at different temperatures.

[0098] like Figure 5 As shown, within the temperature range of 800–650 °C, the polarization impedance of the NBSCF symmetric cell measured at 800 °C, 750 °C, 700 °C, and 650 °C is 0.005 Ω·cm. 2 0.008 Ω·cm 2 0.014 Ω·cm 2 and 0.036Ω·cm 2 The polarization impedance of the NBCF symmetric cell measured at the corresponding temperatures was 0.010 Ω·cm. 2 0.018 Ω·cm 2 0.032 Ω·cm 2 and 0.061 Ω·cm 2 Compared to NBCF, NBSCF exhibits significantly improved oxygen reduction and oxygen evolution reactivity.

[0099] Figure 7 The results of the anti-carbon deposition performance test of the NBSCF symmetric cell under an air atmosphere containing 1% carbon dioxide are shown. First, the electrochemical impedance spectroscopy of the symmetric cell was tested under air atmosphere, with measurements taken every 30 minutes. After 1 hour, the ohmic impedance and polarization impedance of the symmetric cell remained essentially unchanged.

[0100] The test atmosphere was then switched to air containing 1% carbon dioxide. The ohmic impedance and polarization impedance of the symmetrical cell increased rapidly, and then increased slowly with increasing test time. After 150 minutes, the test atmosphere was switched back to air, and the ohmic impedance and polarization impedance of the symmetrical cell returned to their initial values, indicating that the NBSCF air electrode material has good resistance to carbon deposition.

[0101] Test Example 3: This test example performs fuel cell mode performance tests on the proton ceramic fuel cell prepared in Example 5 and the oxygen ion conductor type reversible solid oxide battery prepared in Example 6.

[0102] In the testing of proton ceramic fuel cells, the prepared single cells were sealed on quartz tubes with silver paste, dried in a forced-air drying oven, and then placed in an experimental furnace. The air electrode of the single cell was exposed to an air atmosphere, and pure H2 was introduced as fuel into the fuel electrode side of the single cell. The flow rate of the fuel gas and the test temperature of the single cell were controlled to test the performance of the single cells NBSCF|BZCYYb|Ni-BZCYYb and NBCF|BZCYYb|Ni-BZCYYb at different temperatures.

[0103] Figure 6 Figures (a) and (b) show the current-voltage-power density curves of single cells NBSCF|BZCYYb|Ni-BZCYYb and NBCF|BZCYYb|Ni-BZCYYb, respectively, under H2 atmosphere. At 700℃, 650℃, 600℃, and 550℃, the open-circuit voltage of both single cells is greater than 1 V, indicating that the electrolyte is dense and the single cells are well-sealed.

[0104] The maximum output power density of the single-cell NBSCF|BZCYYb|Ni-BZCYYb at 700℃, 650℃, 600℃ and 550℃ is 1270 mW·cm⁻¹. -2 860 mW·cm -2 540 mW·cm -2 and 210 mW·cm -2 The maximum output power density of the single-cell NBCF|BZCYYb|Ni-BZCYYb at 700℃, 650℃, 600℃, and 550℃ is 850 mW·cm⁻¹. -2 613 mW·cm -2 447 mW·cm -2 and 198 mW·cm -2 The above results demonstrate that the Sr-doped NBSCF air electrode material can significantly improve the output performance of proton ceramic fuel cells using H2 as fuel.

[0105] In the testing of oxygen-ion conductor type reversible solid oxide batteries, the prepared single cells were sealed on a quartz tube with silver paste, dried in a forced-air drying oven, and then placed in an experimental furnace. The air electrode of the single cell was exposed to an air atmosphere, and pure H2 was introduced as fuel into the fuel electrode side of the single cell. The flow rate of the fuel gas and the test temperature of the single cell were controlled to test the performance of the single cells NBSCF|GDC|YSZ|Ni-YSZ and NBCF|GDC|YSZ|Ni-YSZ at different temperatures.

[0106] Figure 8 Figures (a) and (b) show the current-voltage-power density curves of single cells NBSCF|GDC|YSZ|Ni-YSZ and NBCF|GDC|YSZ|Ni-YSZ, respectively, under H2 atmosphere. At 800℃, 750℃, and 700℃, the open-circuit voltage of both single cells is greater than 1 V, indicating that the electrolyte is dense and the single cells are well-sealed.

[0107] The maximum output power density of a single-cell NBSCF|GDC|YSZ|Ni-YSZ at 800℃, 750℃, and 700℃ is 1370 mW·cm³. -2 970 mW·cm -2 and 610 mW·cm -2 The maximum output power density of the single-cell NBCF|GDC|YSZ|Ni-YSZ at 800℃, 750℃, and 700℃ is 1020 mW·cm³. -2 650 mW·cm -2 and 420 mW·cm -2 The above results demonstrate that the Sr-doped NBSCF air electrode material can significantly improve the output performance of oxygen-ion conductor solid oxide batteries using H2 as fuel.

[0108] Test Example 4: This test example performs electrolytic cell mode performance testing on the oxygen ion conductor type reversible solid oxide battery prepared in Example 6.

[0109] The prepared single cells were sealed onto a quartz tube using silver paste, dried in a forced-air drying oven, and then placed in an experimental furnace. The air electrode of the single cell was exposed to air, and wet H2 containing 30% water vapor was introduced into the fuel electrode side of the single cell. The flow rate of the fuel gas and the test temperature of the single cell were controlled to test the water electrolysis performance of the single cells NBSCF|GDC|YSZ|Ni-YSZ at different temperatures.

[0110] Figure 9The current-voltage polarization curves of a single-cell NBSCF|GDC|YSZ|Ni-YSZ in water vapor electrolysis mode at 700~800℃ are shown. As the current density increases, the electrolysis voltage gradually increases. The curves do not show significant concentration polarization limitation in the high current density region, indicating that the single cell has a good water vapor diffusion channel.

[0111] The test temperature has a significant impact on the electrolytic performance of the single cell. At a constant electrolytic voltage of 1.3 V, the current density of the single cell reaches 1.35 A·cm⁻¹ at 800 °C. -2 The current density at 750℃ is 0.6 A·cm. -2 The current density at 700℃ is 0.3 A·cm. -2 .

[0112] High-temperature environments can lower the reaction energy barriers for oxygen evolution at the air electrode and water vapor reduction at the fuel electrode, reducing interfacial polarization losses between the air electrode, electrolyte, and fuel electrode. The single cell can electrolyze water to produce hydrogen within a temperature range of 700–800°C, exhibiting a high electrolysis current density at high temperatures and maintaining effective electrolysis capability at medium temperatures, indicating that the single cell has good temperature adaptability.

[0113] Test Example 5: This test example examines the oxygen ion conductor type reversible solid oxide battery prepared in Example 6 for alternating cycle stability testing in fuel cell mode and electrolyzer mode.

[0114] The prepared single cells were sealed onto a quartz tube with silver paste, dried in a forced-air drying oven, and then placed in an experimental furnace. The air electrode of the single cell was exposed to the air atmosphere, and wet H2 containing 30% water vapor was introduced into the fuel electrode side of the single cell. The flow rate of the fuel gas and the test temperature of the single cell were controlled, and alternating cycle tests in fuel cell mode and electrolyzer mode were conducted at 700℃.

[0115] In fuel cell mode, 0.5 A·cm is applied to a single cell. -2 A constant current density was applied to the single cell, and the output voltage of the single cell was monitored; in electrolytic cell mode, -0.5 A·cm⁻¹ was applied to the single cell. -2 A constant current density was established, and the electrolysis voltage change of a single cell was monitored.

[0116] like Figure 10As shown, the single cell can stably complete multiple bidirectional switching between fuel cell mode and electrolyzer mode at 700℃. No sudden voltage drop or drastic fluctuations were observed during the test. During reversible cycling, the single cell voltage only decreased gradually and slowly, indicating that there was no sudden failure, delamination, or significant elemental segregation at the interface between the air electrode and the electrolyte, demonstrating that the air electrode material has good bidirectional cycling tolerance.

[0117] Test Example 6: This test example examines the long-term stability of the oxygen-ion conductor type reversible solid oxide battery prepared in Example 6.

[0118] The single cell NBSCF|GDC|YSZ|Ni-YSZ was placed under test conditions of 700°C and subjected to a 500 mA·cm⁻¹ pressure. -2 The current density was used to conduct continuous electrolysis tests.

[0119] Figure 11 The voltage-time curve of a single-cell NBSCF|GDC|YSZ|Ni-YSZ at 700℃ is shown. Figure 11 It can be seen that after 300 hours of continuous electrolysis, the voltage of the single cell remained basically stable, indicating that the single cell has good long-term operational stability.

[0120] Figure 12 This image shows a cross-sectional scanning electron microscope (SEM) image of a single-cell NBSCF|GDC|YSZ|Ni-YSZ after long-term stability testing. Figure 12 It can be seen that the interfaces between the layers of the single cell are clear, and there are no obvious cracks, delamination, or large-area air electrode peeling, indicating that the NBSCF air electrode material has good thermochemical stability.

[0121] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. An air electrode material for a solid oxide battery, characterized in that, The chemical formula of the air electrode material is Nd. 0.5 Ba 0.5-x Sr x Co 0.8 Fe 0.2 O 3-δ Where 0.1≤x≤0.5, and δ is the oxygen vacancy content.

2. The air electrode material according to claim 1, characterized in that, x=0.2, the chemical formula of the air electrode material is Nd 0.5 Ba 0.3 Sr 0.2 Co 0.8 Fe 0.2 O 3-δ The air electrode material has a cubic crystal system.

3. A method for preparing the air electrode material according to claim 1, characterized in that, Includes the following steps: Step 1: According to the stoichiometric ratio of Nd, Ba, Sr, Co and Fe in the air electrode material, dissolve Nd(NO3)3·6H2O, Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O and Fe(NO3)3·9H2O in deionized water to obtain a metal salt solution. Step 2: Add ethylenediaminetetraacetic acid, citric acid and ammonia to the metal salt solution, adjust the pH value, and heat and stir until a gel is formed; Step 3: The gel is dried and calcined sequentially to obtain the air electrode material of the solid oxide battery.

4. The method according to claim 3, characterized in that, In step 2, adjust the pH value to 6-8.

5. The method according to claim 3, characterized in that, The drying temperature is 180~250℃ and the time is 1~10h; the calcination temperature is 900~1100℃ and the time is 1~10h, with a heating rate of 1~10℃ / min.

6. The method according to claim 3, characterized in that, The molar ratio of total metal ions, ethylenediaminetetraacetic acid, and citric acid in the metal salt solution is 1:a:b, where 0 < a ≤ 1.2 and 1 ≤ b ≤ 3.

7. The application of the air electrode material according to claim 1 in the air electrode of a solid oxide battery.

8. The application according to claim 7, characterized in that, The solid oxide battery is a proton ceramic fuel cell, and the electrolyte of the proton ceramic fuel cell is BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The fuel electrode is Ni-BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Composite fuel electrode.

9. The application according to claim 7, characterized in that, The solid oxide battery is an oxygen ion conductor type reversible solid oxide battery, and the electrolyte of the oxygen ion conductor type reversible solid oxide battery is (Y2O3). 0.08 (ZrO2) 0.92 The fuel electrode is Ni-(Y2O3). 0.08 (ZrO2) 0.92 Composite fuel electrode.